Detection of Schistosoma mansoni DNA using polymerase chain reaction from serum and dried blood spot card samples of an adult population in North-western Tanzania - Antje Fuss; Humphrey D. Mazigo; Andreas Mueller (Infectious Diseases of Poverty, 2021)
Abstract Background Real-time polymerase chain reaction (PCR) is a sensitive and specific method for diagnosing schistosomiasis. However, this method should be performed in a laboratory, usually located distant from the sample collection site. Therefore, it is important to have fast sampling preservation methods, which allow simple transport prior to DNA extraction and amplification. The aim of this study was to verify if blood samples applied to filter paper are suitable for analysis of Schistosoma mansoni DNA by real-time PCR. Methods A cross-sectional study was conducted among 100 study participants aged 17 to 70 years in a fishing village on the southern shore of Lake Victoria, Tanzania. Serum samples and ethylenediaminetetraacetic acid (EDTA)-anticoagulated whole blood for preparation of dried blood spots (DBS) were collected to test for Schistosoma mansoni infection by real-time PCR. A combined diagnostic reference of positive results of serum-based real-time PCR and the Kato-Katz (KK) method was used for analysis. Sensitivity and negative predictive value (NPV) were calculated. The Wilcoxon signed-rank test was chosen to compare the mean cycle threshold (Ct) values from serum and DBS. Results According to the reference, 92.5% S. mansoni positive samples were determined. The serum-based real-time PCR performed excellently with 95.4% sensitivity, whereas the DBS-based real-time PCR showed a low sensitivity (45.4%). The Ct-values were significantly higher in DBS (median: 37.3) than in serum samples (median: 27.5, P < 0.001), reflecting a lower parasite-specific DNA load on the filter cards. With increasing egg counts, an increase in sensitivity was observed for all methods. The POC-CCA test and the serum-based real-time PCR showed a sensitivity of 100% for medium and severe infections. The DBS real-time PCR showed a sensitivity of only 85.7% even for severe infections. Conclusions DBS-based real-time PCR did not provide good results in our study and therefore should not be recommended or must be tested concerning temperature of storage, storage duration, use of different filter papers and extraction methods before it is used in future studies. In contrast, our results showed that the POC-CCA test is a sensitive and precise test for detecting S. mansoni infections .